Preventing motor vehicle crash injuries and deaths: science vs. folklore lessons from history. Issue 1 (2nd January 2020) - O'Neill, Brian; Mohan, Dinesh
Abstract: Not long after the beginnings of motorization in the early 1900s, deaths and injuries from motor vehicle crashes became a problem in a number of high-income-countries (HIC)s, especially the United States. With the biggest problem the US led early efforts to address this issue, and for six decades these efforts were based on folklore (ie a body of widely held but false or unsubstantiated beliefs). They were not evaluated, but clearly were unsuccessful as crash deaths and injuries continued to rise. It was not until the 1970s that a broader range of countermeasures began to be adopted and was scientifically evaluated, and as a result, crash deaths and injuries declined. This history has important lessons today for many low-and-middle-income countries that have growing numbers of motor vehicle crash deaths and injuries, many of which are pedestrians and motorcyclists. This is because there continue to be advocates for many of the failed approaches (especially educational) that dominated the early efforts in HICs.